Selection strategy of substation distribution unit based on management collaboration theory - Wenjie Xue; Chaoyin An; Tengfei Sheng; Pingxian Dong; Yuxin Zhai; Jinfeng Zhang; Jiewen Shen (Heliyon)
Background: As the comprehensive development demands of power grid companies for substations continue to increase, traditional substation distribution equipment selection strategies, which only consider the life cycle cost theory, are no longer sufficient to meet current requirements. To address this, this paper goes beyond the existing methods that focus solely on economic factors for substation distribution equipment selection. First, the enterprise asset management theory is introduced to preprocess data for substation distribution equipment. Then, the economic aspects of substation distribution equipment are analyzed based on life cycle theory. Simultaneously, reliability-centered maintenance theory is employed to study the reliability of substation distribution equipment, while rough set theory is used to evaluate energy efficiency indicators for the equipment. Finally, an equipment selection strategy is proposed based on the collaborative management theory derived from Total Productive Maintenance (TPM). This study is applied to the historical data of a 110 kV substation in Henan Province for the selection of substation distribution equipment. The results indicate that the proposed selection strategy effectively addresses the comprehensive development needs of substation operations, validates the strategy's effectiveness, and provides theoretical support for the upgrade and renovation of substations in Henan Province.